2018
DOI: 10.1002/app.46415
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of polyethylene binder for heterogeneous ion exchange membrane manufacture to improve its mechanical stability

Abstract: ska Str ansk a, Nat alia V aclav ıkov a MemBrain s.r.o, 471 27 Str a z pod Ralskem, Czech Republic Correspondence to: N. V aclav ıkov a (ABSTRACT: Aim of this work is to propose polymer mixture for heterogeneous ion exchange membrane manufacture to improve membrane mechanical stability. Polyethylene (PE) binders [high-density PE (HDPE), linear low-density PE (LLDPE), metallocenelinear low-density PE (mLLDPE), and their mixtures in various ratios] with ion exchange resins were homogenized and extruded into memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The resin represents particulate filler can contribute to the granulate melting point. It was reported that high ion exchange resin content (60 Wt.%) only slightly decreases the melting point of the membrane granulate comparing to the binder alone (Weinertová et al , 2018a). The granulate was also characterized by thermal analysis with changes in mass (TGA) and heat flow (DTA) simultaneously, as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The resin represents particulate filler can contribute to the granulate melting point. It was reported that high ion exchange resin content (60 Wt.%) only slightly decreases the melting point of the membrane granulate comparing to the binder alone (Weinertová et al , 2018a). The granulate was also characterized by thermal analysis with changes in mass (TGA) and heat flow (DTA) simultaneously, as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%